Tópicos de economía de la regulación de los servicios públicos - Chisari, Omar Osvaldo (2011)
Competitive markets could yield socially optimum results, but although market fail in many cases. If the regulation is successful in generating competition or in replicating its incentives, the next problem to solve is to face the inherent tendency of the competition dynamic toward concentration, cartelization or monopolization of the markets. Mechanisms to ensure or to preserve competition gain importance. Regulation could be conceived as an evolutionary process starting in natural monopoly regulation and ending in competition policy. In many cases, competition is infeasible with the current state of the technology (such as in water and sanitation), whether in other infrastructure sectors it can be possible (such as in segments of telephony or power generation. Regulation is compatible with state provision, and there can be separated the provision, control and supervision of the providers, even when the former are in public hands. Normally tariffs are regulated in infrastructure sectors, also quality and safety standards. Regulation nevertheless is a second best device, since it is costly. We develop a list of topics on market failures, natural monopoly, information problems, different kind of regulatory mechanisms, access prices, the basic Ramsey model of prices, applied to regulation, universal service obligation, the quality of product and service regulation, cost of capital in regulated industries, efficiency and benchmarking, and we conclude discussing the link between infrastructure and growth.